IMPLEMENTASI MANAJEMEN PERGRURUAN TINGGI (STUDI KASUS PADA PTKIS KOPERTAIS WILAYAH VII SUMATERA SELATAN) - Annur, Saipul; Suhono, Suhono; Era Lestari (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2019)
This research was motivated by the facts and phenomena in the development of government policies on higher education governance that were getting tighter, hence “Perguruan Tinggi Keagamaan Islam Swata (PTKIS) requires more intensive administrative and academic coaching, in order to require standard of higher education. The aim of this study was to analyze the problems of private Islamic higher education institutions in Region VII Kopertais in increasing SNP in South Sumatra and how the management of the development of private Islamic higher education in Kopertais VII in increasing SNP in South Sumatra. The researchers used qualitative with the type of descriptive analysis research.Tthe data sources in this study were the Head of the Kopertis II Sumbagsel, Islamic Religious College Leaders, lecturers and employees under the Kopertis II Sumbasel. The research approach uses a Sociological and Phenomenological approach. The results show that PTKIS has tried to carry out a phase of awareness building, physical facilities, academic development, and taking measurements and awards.